2007
DOI: 10.1111/j.1444-2906.2007.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal size distribution, condition status and muscle yield of Mediterranean horse mackerel Trachurus mediterraneus from the North Aegean Sea, Greece

Abstract: The seasonal intrinsic variability of the North Aegean Sea Mediterranean horse mackerel Trachurus mediterraneus population has been studied from monthly samples taken from the Greek purse-seine fishery over a 4-year period (2001)(2002)(2003)(2004)(2005). The length and weight frequency distributions differed significantly by season, the highest mean lengths and weights attained in spring and the lowest in autumn. Length-weight relationships were determined on a monthly and annual basis, and monthly variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…The increased of ponderal index values during reproductive activity was also reported on family Characidae at Brazil river floodplain (Lizama and Ambrósio 2002), Trachurus mediterraneus in the Aegean Sea (Tzikas et al 2007), Johnius belangerii in Mayangan beach, Indonesia (Rahardjo and Simanjuntak 2008), Sardinella atricauda in Kendari Bay, Indonesia (Asriyana 2015), Pseudorhombus triocellatus in Parangipettai Coast, India (Bharadhirajan et al 2019). This phenomenon can be understood as during the time of spawning, the main energy source used for gonadal development and spawning (Lizama and Ambrósio 2002) resulting in the increased values of Gonado Somatic Index (GSI) and ponderal index.…”
Section: Discussionsupporting
confidence: 67%
“…The increased of ponderal index values during reproductive activity was also reported on family Characidae at Brazil river floodplain (Lizama and Ambrósio 2002), Trachurus mediterraneus in the Aegean Sea (Tzikas et al 2007), Johnius belangerii in Mayangan beach, Indonesia (Rahardjo and Simanjuntak 2008), Sardinella atricauda in Kendari Bay, Indonesia (Asriyana 2015), Pseudorhombus triocellatus in Parangipettai Coast, India (Bharadhirajan et al 2019). This phenomenon can be understood as during the time of spawning, the main energy source used for gonadal development and spawning (Lizama and Ambrósio 2002) resulting in the increased values of Gonado Somatic Index (GSI) and ponderal index.…”
Section: Discussionsupporting
confidence: 67%
“…These bacterial isolates are classified into two groups: indigenous and post-harvest bacteria. Previous studies have also demonstrated the presence of indicator microorganisms of fecal pollution, opportunistic and pathogenic bacteria to humans in fish (Tsai et al, 2002;Ferreira and Pinho, 2006;Tzikas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated the presence of indicator microorganisms of fecal pollution, opportunistic and pathogenic bacteria to humans in fish [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%